ChemInform Abstract: Dearomative Radical Spirocyclization from N‐Benzyltrichloroacetamides Revisited Using a Copper(I)‐Mediated Atom Transfer Reaction Leading to 2‐Azaspiro[4.5]decanes. Issue 36 (15th August 2013) - Diaba, Faiza; Montiel, Juan A.; Martinez‐Laporta, Agustin; Bonjoch, Josep
Abstract The process affords dearomatized spirolactams, interesting subunits of various natural products, after hydrolytic work‐up and reveals a significantly limited substrate scope.